The Influence Of Consumer Perception Of Brand On Satisfaction And Purchase Intention: Marketing 4.0 Approach: English - Azmi Agniatussalam; Budi Astuti (Cita konsultindo, 2024)
This research focuses on examining the influence of brand identity, brand image, brand attitude, brand integrity, and brand interaction on consumer satisfaction and consumer buying interest. This research uses the research object Erigo Apparel Store Indonesia using a quantitative approach. The data collection method uses a questionnaire and then the data is processed statistically using Structural Equation Modeling (SEM) using Partial Least Square (PLS). The results of this research show that: 1) Brand identity does not have a positive and significant effect on customer satisfaction, 2) Brand image, brand integrity, brand interaction and brand attitude have a positive effect on customer satisfaction, 3) Brand identity, brand attitude and brand interaction has a positive effect on purchase intention, 4) Brand image and brand integrity do not have a positive effect on purchase intention, and 5) Customer satisfaction has a positive effect on purchase intention. The results of this research demonstrate an important contribution in understanding the factors that influence consumer satisfaction and purchasing intentions, as well as providing strategic guidance for Erigo Stores in improving brand performance and interactions with customers.